Prevention of eye diseases among the residents of Lublin, Poland - Piotr Kozłowski; Magdalena Kozłowska; Karolina Kozłowska (Kazimierz Wielki University, 2017)
The aim of the study was to evaluate the behavior and habits of prevention eye diseases. The study included 132 participants. In the study group, 59,1% of respondents were females whereas 40,9 were males. The age of participants ranged from 18 to 64 years. The study conducted in the period from Mary 2016 to January 2017 and it employedstandardized interview research method. Research tool, which was used for data collection was a questionnaire consisted of 18 questions single-choice questions. Statistical analysis was performed using the chi-square test. All values for which p <0.05 (probability of error) were considered statistically significant. Respondents were asked about education, work and knowledge about eye diseases. 61,4% of respondents responded that they meet an ophthalmologist only when they have visual problem (p <0.05). Regularly every two to three years, preventive eye examinations performed by 9.1% of respondents, more often female. Less than once every 3 years, preventive eye examinations are done by 12.1%, the rest of the respondents are doing less than every 5 years. In the group of respondents surveying less than 5 years (17.4%) were mainly young people at the age of 18-30 (91.3% of respondents). This is a very disturbing result, as regular eye prevention should be conducted regularly from an early age. 12.1% of respondents doing research less than 3 years and less than 5 years (17.4%) are mainly older than 50 years of age. It is definitely too sporadic to effectively prevent eye diseases, especially those that develop slowly and asymptomatically as cataracts. The respondents were also asked whether they had a visual impairment: 46.2% said they had it, 24.3% said they had no eye defect, and 29.5% said they did not know if their eyesight was affected. defect. Respondents who admitted that they had knowledge about their eye defect most often doubled that they suffered from farsightedness -73.8%. More than two thirds of respondents who acknowledged that they know of eye defects admitted that they wear sunglasses regularly (68.9%), only 13.1% of respondents occasionally use glasses in this group. Eyewear does not use despite knowledge that only 18% of respondents are needed. These results indicate that respondents who regularly visit an ophthalmologist more often wear eyeglasses, only a small group (31.1%) respondents do not do so for various reasons, perhaps due to lack of awareness and knowledge of what is harmful. 16.7% of respondents admitted wearing contact lenses.